2016
DOI: 10.7567/apex.9.022102
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid tunnel junction contacts to III–nitride light-emitting diodes

Abstract: In this work, we demonstrate highly doped GaN p–n tunnel junction (TJ) contacts on III–nitride heterostructures where the active region of the device and the top p-GaN layers were grown by metal organic chemical vapor deposition and highly doped n-GaN was grown by NH3 molecular beam epitaxy to form the TJ. The regrowth interface in these hybrid devices was found to have a high concentration of oxygen, which likely enhanced tunneling through the diode. For optimized regrowth, the best tunnel junction device had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
86
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 24 publications
(34 reference statements)
2
86
1
Order By: Relevance
“…Secondary-ion mass spectrometry and Halleffect measurements revealed that the doping efficiency of PSD n-type GaN is close to unity at electron concentrations as high as 5.1 × 10 20 cm 3 . A record low resistivity for n-type GaN of 0.16 mΩ cm was achieved with an electron mobility of 100 cm 2 V 1 s 1 at a carrier concentration of 3.9 × 10 20 cm 3 . We explain this unusually high electron mobility of PSD n-type GaN within the framework of conventional scattering theory by modifying a parameter related to nonparabolicity of the conduction band.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary-ion mass spectrometry and Halleffect measurements revealed that the doping efficiency of PSD n-type GaN is close to unity at electron concentrations as high as 5.1 × 10 20 cm 3 . A record low resistivity for n-type GaN of 0.16 mΩ cm was achieved with an electron mobility of 100 cm 2 V 1 s 1 at a carrier concentration of 3.9 × 10 20 cm 3 . We explain this unusually high electron mobility of PSD n-type GaN within the framework of conventional scattering theory by modifying a parameter related to nonparabolicity of the conduction band.…”
mentioning
confidence: 99%
“…The excellent electrical properties presented in this letter clearly demonstrate the striking advantages of the low-temperature PSD technique for growing high-quality and highly conductive n-type GaN The physics of degenerate electrons in a partially filled conduction band of heavily doped n-type GaN has been extensively investigated because of the importance for reducing the parasitic resistance of nitride optical and electron devices. [1][2][3] Si is the most commonly used dopant for n-type GaN, and a room-temperature (RT) free-electron concentration of 3.6 × 10 20 cm 3 has been achieved in Si-doped GaN deposited using molecular beam epitaxy (MBE). 3 Ge is also used as an alternative dopant to Si.…”
mentioning
confidence: 99%
“…Our TJ design allowed us to achieve a differential resistivity lower than 10 −4 Ω·cm 2 for current densities higher than 2 kA=cm 2 , which is very promising for LD applications and is one of the best results among those reported in the literature. 4,8,23,29) An interesting remark can be given from the comparison of the differential resistivities of the standard LD, TJ LD, and test TJ n=p ++ =n ++ structure. Figure 4 shows the differential resistivities of the standard PAMBE and TJ LDs (the I-V characteristics of which are depicted in Fig.…”
mentioning
confidence: 99%
“…Promising results for new types of edge-emitting LD or VCSEL have been reported recently for hybrid MOVPE=MBE growth in which the active part of the device was grown by MOVPE and the p-n TJ was made by MBE. [8][9][10]20) The p-n tunnel junction was demonstrated for narrowbandgap materials in 1958. 21) The theory of the p-n TJ indicates that the transmission probability of carriers through such a junction depends on the depletion width.…”
mentioning
confidence: 99%
See 1 more Smart Citation